Scoping study of KOS registries - Tudhope, Douglas (2007)
A 6 month Joint Information Systems Committee (JISC) funded project on a terminology registry scoping study led by UKOLN in collaboration with Glamorgan and OCLC is just starting. This study aims to analyse issues related to potential delivery of a Terminology Registry as a shared infrastructure service within the JISC Information Environment. It will consider how a Registry might support development of terminology and other services within the context of a services oriented environment.